2006
DOI: 10.1152/ajpheart.00751.2005
|View full text |Cite
|
Sign up to set email alerts
|

Use of simultaneous pressure and velocity measurements to estimate arterial wave speed at a single site in humans

Abstract: . Use of simultaneous pressure and velocity measurements to estimate arterial wave speed at a single site in humans. Am J Physiol Heart Circ Physiol 290: H878 -H885, 2006. First published August 26, 2005 doi:10.1152/ajpheart.00751.2005.-It has not been possible to measure wave speed in the human coronary artery, because the vessel is too short for the conventional two-point measurement technique used in the aorta. We present a new method derived from wave intensity analysis, which allows derivation of wave sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
127
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(132 citation statements)
references
References 31 publications
(40 reference statements)
4
127
0
1
Order By: Relevance
“…While the AO-PWV1 is the regional PWV of the ascending aorta, the AO-PWV2 reflects the mean PWV of 2 points between the ascending and thoracic aorta, so their values are naturally expected to differ. According to previous studies, the normal AO-PWV2 in middle-aged people is about 5-8 m/s, [19][20][21][22] being close to the mean AO-PWV1 and AO-PWV2 values observed in this study. Comparison of the regional PWV values in the human aorta showed that the values increase at more peripheral sites.…”
Section: Discussionsupporting
confidence: 89%
“…While the AO-PWV1 is the regional PWV of the ascending aorta, the AO-PWV2 reflects the mean PWV of 2 points between the ascending and thoracic aorta, so their values are naturally expected to differ. According to previous studies, the normal AO-PWV2 in middle-aged people is about 5-8 m/s, [19][20][21][22] being close to the mean AO-PWV1 and AO-PWV2 values observed in this study. Comparison of the regional PWV values in the human aorta showed that the values increase at more peripheral sites.…”
Section: Discussionsupporting
confidence: 89%
“…Pulse wave velocity was estimated using the single point method described by Davies et al 17 This produces the same waveform separation as an analysis in the frequency domain.…”
Section: Waveform Post Processingmentioning
confidence: 99%
“…Pulse wave velocity was estimated using the single point method described by Davies et al 17 This produces the same waveform separation as an analysis in the frequency domain. 18 Aortic flow velocity waveforms were integrated over time and multiplied by aortic cross-sectional area …”
Section: Waveform Post Processingmentioning
confidence: 99%
“…Several different methods of obtaining regional pulse wave velocity, c, in an artery have been reported by Khir et al [16,17], Davies et al [6], and ourselves [10]. Our wave intensity measurement system uses the two methods proposed by ourselves.…”
Section: Separation Of Wave Intensity Into the Forward And Backward Cmentioning
confidence: 99%